(3dWGFa Gdeff aj efGbH GdTjN CHj GdYHGS GdeQSi hTjNg CHj GdMSf GdTGPdis - (3CMeO Hf eMeO Hf YHO GdcQje Hf YWGA Gddg GdScfOQj, GHf YWGA Gddg , JGL GdOjf CHh GdaVd,J (B709 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aJM dChdjGFg HGH eMJHg s
(3BNQgG (B:s
(3EfeG jhai GdUGHQ ef CLQge s
(3HBNQgG bQGAI dgG ef GdTjN YHOGdaJGM GdfMhi Ydi GdTjN eMeO GdQedi GdTGaYis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B121s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B118 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B252 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYg GdCeQjcjI ai HjQhJ s
Keywords: (3GdJGQjNs